Can the FIFA World Cup Football (Soccer) Tournament Be Associated with an Increase in Domestic Abuse?. (May 2014) - Kirby, Stuart; Francis, Brian; O'Flaherty, Rosalie
Objectives: This study aims to establish whether empirical evidence exists to support the anecdotal view that the Fédération Internationale de Football Association world cup football (soccer) tournament can be associated with a rise in reported domestic abuse incidents, when viewed remotely via television. Method: A quantitative analysis, using Poisson and negative binomial regression models looked at monthly and daily domestic abuse incidents reported to a police force in the North West of England across three separate tournaments (2002, 2006, and 2010). Results: The study found two statistically significant trends. First, a match day trend showed the risk of domestic abuse rose by 26 percent when the English national team won or drew, and a 38 percent increase when the national team lost. Second, a tournament trend was apparent, as reported domestic abuse incidents increased in frequency with each new tournament. Conclusion: Although this is a relatively small study, it has significant ramifications due to the global nature of televised football (soccer) tournaments. If replicated, it presents significant opportunities to identify and reduce incidents of domestic abuse associated with televised soccer games.